PERANAN PENDIDIKAN KEWARGANEGARAAN (PKN) DALAM PEMBENTUKAN MORAL PESERTA DIDIK - Syamsul, Yuliana; Widodo, Rohmad; Tinus, Agus (Jurnal Civic Hukum, 2017)
Moral is somebody?s act/attitude/speech in interacting with others. If what is conducted by somebody suitable with value in society and can be accepted also please the surrounding, he/she is regarded as having good moral. By using SMK Muhmmadiyah 2 Malang as the object, the researcher conducts a study on ?The role of civics (PKn) in building students? moral in SMK Muhammadiyah 2 Malang?.This study is aimed to know the problems on the focus of study; they are: (1) How is the role of civics in building students? moral in SMK Muhammadiyah 2 Malang? (2) What obstacles faced in building students? moral in SMK Muhammadiyah 2 Malang? (3) What are the solutions to overcome the obstacles in building students? moral in SMK Muhammadiyah 2 Malang? This study used qualitative approach. To obtain the data, the researcher used observation, interview and documentation. Meanwhile, for checking data validity, the researcher used credibility, transferability, dependability and confrmability.From the result of study, it is obtained that the role of civics in building students? moral in SMK Muhammadiyah 2 Malang is by embedding responsibility, caring, discipline and nationality also teach students on religious. Yet, in building students? moral, there are obstacles such as the less of parents? attention and comprehension and society so that children often do something which harms them. To overcome the obstacles, the teachers are expected that there is still good cooperation between teacher, parent and society.